2009
DOI: 10.1203/pdr.0b013e31819ed7a8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Bifidobacteria on the Establishment of Bifidobacteria Colonizing the Gut in Infants

Abstract: ABSTRACT:The aim of this study was to examine the influence of maternal intestinal and vaginal bifidobacteria on the establishment of bifidobacteria colonizing the gut in infants. Fecal samples from 110 healthy pregnant mothers within 1 mo before delivery and their babies at 1 mo of age and 100 vaginal swabs from the mother within 7 d before delivery were collected at a maternity hospital in Fukuoka city, Japan. The fecal and vaginal samples were assayed by PCR to detect Bifidobacterium species and by real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
62
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 32 publications
6
62
4
1
Order By: Relevance
“…In fact, the isolation of bifidobacteria from human milk has been reported (9, 10), even though it is currently not known how bifidobacteria reach this human bodily fluid (11). In addition, PCR-based approaches have provided suggestive evidence for the occurrence of direct transmission of bifidobacterial strains and other gut commensals from mother to newborn (12)(13)(14).In this study, we investigated this notion of vertical transmission of bifidobacteria from mother to newborn by assessing the gut and milk microbiomes of four mother-child sample sets, revealing the existence of shared bifidobacterial strains. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the isolation of bifidobacteria from human milk has been reported (9, 10), even though it is currently not known how bifidobacteria reach this human bodily fluid (11). In addition, PCR-based approaches have provided suggestive evidence for the occurrence of direct transmission of bifidobacterial strains and other gut commensals from mother to newborn (12)(13)(14).In this study, we investigated this notion of vertical transmission of bifidobacteria from mother to newborn by assessing the gut and milk microbiomes of four mother-child sample sets, revealing the existence of shared bifidobacterial strains. …”
mentioning
confidence: 99%
“…In fact, the isolation of bifidobacteria from human milk has been reported (9, 10), even though it is currently not known how bifidobacteria reach this human bodily fluid (11). In addition, PCR-based approaches have provided suggestive evidence for the occurrence of direct transmission of bifidobacterial strains and other gut commensals from mother to newborn (12)(13)(14).…”
mentioning
confidence: 99%
“…Recent studies have also discussed that breast milk can be another source of intestinal microbes (20,22,28,31). Several studies employing molecular biology techniques have suggested the possibility of vertical mother-toinfant transmission of intestinal microbes (1,25,26,32) and the presence of these microorganisms in breast milk (12,21,28). However, the molecular methods used in those studies, such as real-time quantitative PCR (qPCR), while effective in identifying microorganisms at the species level, do not allow comparisons at the strain level.…”
mentioning
confidence: 99%
“…Bacterial DNA from the samples was analyzed by real-time PCR to count the lactobacilli according to the method reported by Mikami et al (16). The Lactobacillus genus-specific paired primers, LactoF (5Ј-TGGAAACAGRTGCTAATACCG-3Ј) and LactoR (5Ј-GTCCATTGTGGAAGATTCCC-3Ј), used in this study have been described previously by Byun et al (5).…”
Section: Methodsmentioning
confidence: 99%
“…The composition of Lactobacillus species in the stomachs of SPF mice was examined using 11 different species-specific primers reported by Walter et al (26). The extraction of bacterial DNA from the stomach and PCR amplification were done according to a method described elsewhere (16).…”
Section: Methodsmentioning
confidence: 99%